2018
DOI: 10.1103/physrevlett.120.120401
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-Space Josephson Effects

Abstract: The Josephson effect is a prominent phenomenon of quantum supercurrents that has been widely studied in superconductors and superfluids. Typical Josephson junctions consist of two realspace superconductors (superfluids) coupled through a weak tunneling barrier. Here we propose a momentum-space Josephson junction in a spin-orbit coupled Bose-Einstein condensate, where states with two different momenta are coupled through Raman-assisted tunneling. We show that Josephson currents can be induced not only by applyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…In order to understand the origin of this degeneracy we look into the distribution of the tunneling current initiated by these excitations. The transverse tunneling current density can be written in the following form Inserting here the wave function (12,13) we get…”
Section: General Properties Of the Bogoliubov Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand the origin of this degeneracy we look into the distribution of the tunneling current initiated by these excitations. The transverse tunneling current density can be written in the following form Inserting here the wave function (12,13) we get…”
Section: General Properties Of the Bogoliubov Spectrummentioning
confidence: 99%
“…These effects have been initially studied for coupled condensates in double-well traps [1][2][3][4][5][6] and coherently coupled spinor condensates [7,8]. In recent years Josephson effects were also observed and analyzed in more exotic systems such as fermionic superfluids [9], polariton condensates [10], spin-orbit coupled BECs [11,12] and condensates with attractive interaction [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Rabi oscillations shown here are driven by a weak lattice which is slightly stronger than the mean field interaction strength. This character may be indicative of the dynamics underlying momentum-space Josephson junctions [37], which is beyond the scope of these experimental observations.Stripe-phase ground state stability. While previous arguments have indicated that we reliably prepare the appropriate spin-momentum mixtures to achieve a highcontrast stripe-phase, those mixtures must be coherent over a long period of time to produce the expected density modulation for further investigation of dynamical 0.0 0.5 1.0 1.5 2.0 Time after quench [ms] −1.0 −0.5 0.0 0.5…”
mentioning
confidence: 94%
“…However, recent works have attempted to sidestep these difficulties in creative ways, leading to experimental observations of some signatures of superfluid stripe phases in different systems [31][32][33][34].Despite these significant advances, the quest for a robust and long-lived platform for the experimental investigations of stripe-phase properties remains. In this Letter, we show that the superposition of two local band minima to form a supersolid-like ground state can be robustly achieved by means other than atomic interactions.Specifically, we engineer momentum-space hopping between two local band minima in a SOC BEC driven by a weak optical lattice [35][36][37]. The coupling between different momenta through static or moving optical lattices has been widely used in ultracold atomic gases for engineering versatile types of physics [38][39][40][41], but momentum states involved in such coupling schemes are usually not local band minima and thus have short lifetime.…”
mentioning
confidence: 99%
“…This has opened a whole new research field of strongly correlated systems with potential applications in quantum technology and quantum simulation of condensed-matter problems [4][5][6][7][8]. One such well-studied example is the system of a few interacting bosons in a double-well potential [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].BEC in a symmetric double-well potential, popularly known as the bosonic Josephson junction (BJJ) [29], provides a paradigm model which is used to study many fundamental quantum features like quantum entanglement [30], and to construct atom interferometers such as a Mach-Zehnder interferometer [31]. BJJ dynamics has been studied quite thoroughly both theoretically and experimentally [9-13, 19, 22, 29, 32-50].…”
mentioning
confidence: 99%